Reprogramming of the Hevea brasiliensis Epigenome and Transcriptome in Response to Cold Stress - Tang, Xiao; Zhang, Yonglei; Yuan, Hong-Mei; Zhai, Jinling; Huang, Xi (Frontiers in Plant Science, 2022)
Low temperature is a key factor limiting the rubber plantation extending to high latitude area. Previous work has shown that cold-induced DNA demethylation was coordinated with the expression of cold-responsive (COR) genes in Hevea brasiliensis. In this work, reduced representation bisulphite sequencing (RRBS) analysis of H. brasiliensis showed that cold treatment induced global genomic DNA demethylation and altered the sequence contexts of mCpG islands, but the levels of mC methylation in transposon elements (TEs) were enhanced by cold treatment. Integrated analysis of the DNA methylome and transcriptome revealed 400 genes whose expression correlated with altered DNA methylation. DNA demethylation in the upstream region of gene seems to correlate with higher gene expression, whereas demethylation in the gene body has less association. Our results suggest that cold treatment globally change the genomic DNA methylation status of the rubber tree, which might coordinate reprogramming of the transcriptome.